2011
DOI: 10.4028/www.scientific.net/amm.145.78
|View full text |Cite
|
Sign up to set email alerts
|

Application of TRACE and CFD in the Spent Fuel Pool of Chinshan Nuclear Power Plant

Abstract: In the nuclear power plant (NPP) safety, the safety analysis of the NPP is very important work. In Fukushima NPP event, due to the earthquake, the cooling system of the spent fuel pool failed and the safety issue of the spent fuel pool generated. After Fukushima NPP event, INER (Institute of Nuclear Energy Research, Atomic Energy Council, R.O.C.) performed the safety analysis of the spent fuel pool for Chinshan NPP which also assumed the cooling system of the spent fuel pool failed. The geometry of the Chinsha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Besides, the top of fuel rod contains springs. Second, this study used TRACE analysis results as boundary condition to calculate the cladding performance by FRAPCON-3.4 under the cooling system failed of spent fuel poor for Chinshan NPP [4]. The TRACE model of the Chinshan NPP spent fuel pool is 12.17 m × 7.87 m × 11.61 m and the initial condition is 60 ℃ / 1.013 × 10 5 Pa.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the top of fuel rod contains springs. Second, this study used TRACE analysis results as boundary condition to calculate the cladding performance by FRAPCON-3.4 under the cooling system failed of spent fuel poor for Chinshan NPP [4]. The TRACE model of the Chinshan NPP spent fuel pool is 12.17 m × 7.87 m × 11.61 m and the initial condition is 60 ℃ / 1.013 × 10 5 Pa.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The second step is the application of FRAPCON-3.4 in the spent fuel pool of Chinshan NPP. By using the TRACE analysis results as the input data of FRAPCON-3.4 [4], FRAPCON-3.4 can calculate the temperature, hoop stress, oxide thickness of cladding in spent fuel pool.…”
Section: Introductionmentioning
confidence: 99%
“…In this work a model for RELAP-5 to simulate the spent fuel pools is used to analyze the evolution of water evaporation and spent fuel uncovering. Finally, in (Wang et al , 2012), the loss of cooling in Chinshan nuclear power plant is simulated using FLUENT and TRACE codes.…”
Section: In Order To Improve the Spent Fuel Pools Safety Analysis Itmentioning
confidence: 99%
“…The Tehran research reactor (TRR) make-up water system was investigated in their work. Assuming the loss of cooling system for the SFP located at the Chinshan NPP in Taiwan, Wang et al (2012) adopted the TRACE code coupled with the CFD method to study the safety issue related to the SFP. Their results showed that the fuel uncover may occur about 2.7 days after the loss of cooling system in the SFP.…”
Section: Introductionmentioning
confidence: 99%